Size Sensitive Transport Behavior of Liquid Metallic Mixtures - Singh, Bhrigunandan Prasad; Koirala, Ishwar (Journal of Institute of Science and Technology, 2015)
We have used a formalism that connects thermodynamic and transport properties. The formalism has been used to calculate the Gibb’s free energy of mixing, concentration fluctuations in the long wavelength limit, diffusion coefficients and viscosity in Cu-Tl, Cu-Pb and Sn-Tl binary liquid alloys at 1573K, 1473K and 723K respectively with aid of size effect and no size effect. Our calculations show that appreciable size ratio has more effects on the transport properties as compared to thermodynamic properties of homo-coordinated liquid alloys Cu-Tl, Cu-Pb and Sn-Tl. Journal of Institute of Science and Technology, 2015, 20(2): 140-144